Diarrhoea in childhood and cause-specific mortality in older age: analyses of 5642 deaths in 33,261 individuals from the Hertfordshire studies. - Batty, G; Smith, G; Cooper, C; Gale, C (2008)
The objective of these analyses were to examine if episodes of diarrhoea in childhood are related to adult coronary heart disease (CHD) mortality. Data were pooled from two prospective UK cohort studies (participants born 1923--1939). Reported diarrhoea in infancy (3.1%) and between 1 and 5 years (1.1%) was rare. No relationship between diarrhoea in infancy and CHD mortality or mortality from all-causes and cardiovascular disease was observed. Although diarrhoea between 1 and 5 years was also not related to CHD risk, slightly lower rates of total and cardiovascular disease mortality were apparent in this group relative to the diarrhoea-free. In the largest study to date to examine the relation, there was no evidence that diarrhoea in early life had an influence on later CHD mortality.